Enantioanalysis of Leucine in Whole Blood Samples Using Enantioselective, Stochastic Sensors - Raluca-Ioana Stefan-van Staden; Oana-Raluca Musat (Chemosensors, 2023)
Enantioanalysis of amino acids became a key factor in the metabolomics of cancer. As a screening method, it can provide information about the state of health of patients. The main purpose of the study is to develop a highly reliable enantioanalysis method for the determination of D-, and L-leucine in biological samples in order to establish their role as biomarkers in the diagnosis of breast cancer. Two enantioselective stochastic sensors based on N-methyl-fullero-pyrrolidine in graphite and graphene nanopowder pastes were designed, characterized, and validated for the enantioanalysis of leucine in whole blood. Different signatures were recorded for the biomarkers when the stochastic sensors were used, proving their enantioselectivity. In addition, limits for detection on the order of ag L−1 were recorded for each of the enantiomers of leucine when the proposed enantioselective stochastic sensors were used. The wide linear concentration ranges facilitated the assay of the L-leucine in healthy volunteers, and also in patients confirmed with breast cancer. Recoveries of one enantiomer in the presence of the other enantiomer in whole blood samples, higher than 96.50%, proved that the enantioanalysis of enantiomers can be performed reliably from whole blood samples.